Comparative analysis of bioactive compounds and antioxidant activity of Malaysian gingers affected by different drying and extraction methods - Sarmilaah Dewi, Subramaniam (2023)
Ginger (Zingiber officinale Roscoe) has been used as a food, spice, supplement and flavoring ingredient as well as traditional medicines due to its unique features like pungency, aroma, nutrition, and pharmacological activity. Bentong ginger (BG), grown in a high-altitude area of Bentong, Malaysia, has a similar scientific name to the common ginger species and been patented by the Malaysian government. Ginger has a wide range of biological effects, including antioxidant, antimicrobial, anti-cancer, anti-inflammatory, and other effects as it is rich in various bioactive constituents. However, drying and extraction techniques have a significant impact on the bioactive constituents of ginger. The use of higher temperature processing methods may result in the loss of volatile aromatic compounds, a decrease in antioxidant activity, and the degradation of useful nutrient content. Hence, this study presents the effect of different drying techniques with low thermal approach (swirling fluidized bed drying (SFBD), oven drying (OD) and freeze drying (FD)) on the drying kinetics, antioxidant potential, and bioactive compounds of BG. Seven mathematical models were applied to the experimental data to determine the best thin-layer drying models for drying applications. The experimental results showed that SFBD reduces the total drying time compared to OD and FD, which translates to a low energy consumption, high drying rate and moisture diffusivity. In addition, the dried BG sample from the SFBD exhibited a slightly higher 2,2-diphenyl-1-picrylhydrazyl (DPPH) inhibition and total phenolic content (TPC) yield. The Midilli-Kucuk model showed the best fit at explaining the thin layer drying behavior of the BG for OD and SFBD, whereas the Page model showed the best fit for FD. Second objective focuses on the optimization of ultrasonic assisted extraction process variables for a higher yield of phenolic compounds from BG. One-Factor-Analysis and Central Composite Design from Response Surface Methodology were employed to screen and optimize the effect of amplitude, sonication time and solvent concentration towards TPC and DPPH inhibition. The optimized conditions for higher yield of TPC and DPPH inhibition were observed to be amplitude of 32.00 %, sonication time of 14.94 min and solvent (ethanol) concentration of 82.00 %. According to the findings of the study, BG extracts could be a potential antioxidant agent for the food and pharmaceutical industries. Hence, this study also conducted to analyze the potential of optimized BG extracts at different concentrations (5, 10 and 20 % v/v) incorporated in plasticized bio-nanocomposite matrix for the development of active film packaging. The bio-nanocomposite film with 20% BG showed the best improvement on its tensile strength, elongation at break, thickness, opacity, water solubility and moisture content. Antioxidant release test showed continuous release of antioxidant and total phenolic content in 95 % of food simulants for 28 days. This study validated that incorporation of BG extract can be a promising natural additive for active packaging materials.